2020
DOI: 10.1101/2020.05.04.075580
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Importin α2 association with chromatin: Direct DNA binding via a novel DNA binding domain

Abstract: AbstractThe nuclear transport of proteins is important for facilitating appropriate nuclear functions. The proteins of the importin α family play key roles in nuclear transport as transport receptors for a huge number of nuclear proteins. Additionally, these proteins are also reported to possess other functions, including chromatin association and gene regulation. However, these non-transport functions of importin α are not yet fully understood, especially its molecular interac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 75 publications
(115 reference statements)
1
4
0
Order By: Relevance
“…Differences in binding propensities such as those revealed here are also be found in other IBB domain binding molecules, such as DNA (Jibiki et al, 2021) and Rbbp4 (Tsujii et al, 2015). Moreover, as importin α plays an important role in multiple cellular events (Oka & Yoneda, 2018), there may exist additional unknown binding partners.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Differences in binding propensities such as those revealed here are also be found in other IBB domain binding molecules, such as DNA (Jibiki et al, 2021) and Rbbp4 (Tsujii et al, 2015). Moreover, as importin α plays an important role in multiple cellular events (Oka & Yoneda, 2018), there may exist additional unknown binding partners.…”
Section: Resultssupporting
confidence: 67%
“…For example, K42 is retained by all consensus sequences and is highly conserved among species (Data S4). This residue is thought to be involved in binding to DNA (Jibiki et al, 2021) and Rbbp4 (Tsujii et al, 2015) and may be important for such functions. In addition, the biochemical/physicochemical propensity of small bulkiness was conserved at position 21, though the residue differed among family members (Figures S16 and S17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When KPNA2 is only present in the cytoplasm, it can anchor proteins in the cytoplasm; however, when present in both nucleus and cytoplasm, it could be working as a nucleocytoplasmic transporter or as a regulator of gene expression in association with chromatin. 40 The fact that in Kpna2 -KO mice the number of produced spermatozoa is not affected indicates that KPNA2 is not essential until the protein is present in the nucleus at pachytene spermatocyte and spermatid stages, suggesting that at these stages its function may not be compensated by other importin αs. In agreement with this, we found that most DEGs occurred in spermatocytes and spermatids.…”
Section: Discussionmentioning
confidence: 99%
“…Besides a nuclear import role, KPNA2 may also act in the nucleus of late spermatocytes and spermatids by associating with chromatin via its direct DNA-binding ability, promoting gene expression. This feature, which has been examined in embryonic stem cells, 40 should be further explored to determine whether KPNA2 binds to DNA in spermatogenic cells. Whether through the regulation of transcription factors transported to the nucleus or through the control of expression due to its direct association with chromatin, KPNA2 was observed here to exert a specific control of the expression of gene clusters present in certain chromosomes.…”
Section: Discussionmentioning
confidence: 99%